Pengetahuan Petani Padi Terhadap Perubahan Iklim di Kecamatan Balai Kabupaten Sanggau - Emeliani, Monika; Kurniati, Dewi; Komariyati, Komariyati (Hasanuddin University, 2025)
Climate change has become a serious challenge for the agricultural sector, especially rice, a major commodity in Indonesia and highly vulnerable to the impacts of climate change, which increases the risk of crop failure due to unstable seasonal patterns that are difficult to predict. The purpose of this study was to determine the level of rice farmers' knowledge of climate change and to identify the factors that influence their knowledge of climate change. This study was conducted from October 2024 to January 2025 in Balai District, Sanggau Regency. Data collection methods included interviews structured into questionnaires, literature studies, and observations. Data analysis methods used were Likert scale and ordinal logistic regression. The results of the study indicate that the level of knowledge of rice farmers regarding climate change is in the “know” category with a percentage of 75%, meaning that most farmers have good knowledge regarding climate change experienced directly in the field. Farmer knowledge is influenced by factors of education, age, farming experience, land area and access to information, has a good level of feasibility, with a Nagelkerke R² value of 0.652. This means it is able to explain 65.2% of the variation in rice farmers' knowledge regarding climate change. Increasing farmer knowledge is important to support agricultural adaptation efforts through the use of climate-resistant rice varieties, the implementation of cropping patterns, intercropping, and efficient water management as well as strengthening climate resilience in agricultural systems and maintaining food security in the future.